FROM COEXISTENCE TO MUTUALISM: MAINSTREAMING BIODIVERSITY IN THE SUSTAINABLE DEVELOPMENT GOALS: Repositioning Biodiversity as the Foundation for All Development Goals - Ari Budi Suryawinata; Mariel Tania Darmayani; Listyani Suhargo (BIOTROPIA, 2026)
ARTICLE HIGLIGHTS- Mutualism paradigm aligns biodiversity with sustainable development. - Biodiversity acts as a driver for prosperity rather than a constraint. - Integrated policy mixes unlock powerful synergies for global goals. - Reciprocal benefits are vital to moving beyond mere coexistence.ABSTRACTMainstreaming biodiversity into the Sustainable Development Goals (SDGs) is currently hampered by a prevailing “coexistence” paradigm, which treats conservation and economic development as separate, often conflicting domains. This fragmentation leads to persistent policy silos and unresolved trade-offs, undermining long-term sustainability. This study aimed to critically diagnose the structural limitations of this approach and proposes a transition toward “mutualism”—a framework where biodiversity and development objectives are mutually reinforcing. Adopting a critical review methodology, we synthesized evidence from policy, economic, and scientific sectors. We analyzed specific instruments, such as Nature-based Solutions (NbS) and Payments for Ecosystem Services (PES), to identify the institutional, financial, and social barriers currently constraining their effectiveness. The novelty of this paper lies in the conceptualization of ‘mutualism’ not merely as an ecological metaphor, but as an operational framework for the SDGs that moves beyond the traditional “do no harm” principle to actively engineering reciprocal benefits. We concluded that while existing instruments show promise, they fail to achieve systemic change due to a lack of strategic alignment. To operationalize mutualism, we recommend a strategic shift focusing on three pillars: implementing coherent policy mixes that integrate regulatory and fiscal instruments, establishing inclusive governance to manage trade-offs, and mobilizing finance that rewards verifiable ecological and social synergies.